The complete mitochondrial genome of Gyrodactylus pseudorasborae (Platyhelminthes: Monogenea) with a phylogeny of Gyrodactylidae parasites - Xinyi Zeng; Ye Li; Yang Liu; Yaoying Chen; Yajing Liu; Mengwei Song; Tao Chen (BMC Genomics)
Abstract Background Gyrodactylus von Nordmann, 1832, a genus of viviparous parasites within the family Gyrodactylidae, contains one of the largest nominal species in the world. Gyrodactylus pseudorasborae Ondračková, Seifertová & Tkachenko, 2023 widely distributed in Europe and China, although its mitochondrial genome remains unclear. This study aims to sequence the mitogenome of G.pseudorasborae and clarify its phylogenetic relationship within the Gyrodactylidea. The mitochondrial genome of G. pseudorasborae was amplified in six parts from a single parasite, sequenced using primer walking, annotated and analyzed using bioinformatic tools. Results The mitochondrial genome of G. pseudorasborae is 14,189 bp in length, containing 12 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosomal RNA genes (rRNAs), and two major non-coding regions (NCR: NC1 and NC2). The overall A + T content of the mitogenome is 73.1%, a medium content compared with all reported mitochondrial genomes of monogeneans. The mitogenome of G. pseudorasborae presents a clear bias in nucleotide composition with a negative AT skew and a positive GC skew except for NCR. All tRNAs have the typical cloverleaf secondary structure except for tRNA Cys , tRNA Ser1 , and tRNA Ser2 , which lack the dihydrouridine (DHU) arm. Furthermore, one repetitive non-coding region of 32 bp repeats occurred in the NC1 region with poly-T stretch, stem-loop structure, and TAn motif. The gene order is identical to the mitochondrial genomes reported from other Gyrodactylus species except Gyrodactylus nyanzae Paperna, 1973 and Gyrodactylus sp. FZ-2021. Phylogenetic analyses show that G. pseudorasborae and Gyrodactylus parvae You, Easy & Cone, 2008 cluster together with high nodal support based on 12 PCGs sequences and amino acid sequences, Gyrodactylidae forms independent monophyletic clade within Gyrodactylidea. Conclusion Both the mitochondrial genome and phylogenetic analyses support G. pseudorasborae is a member of the genus Gyrodactylus and Gyrodactylidae forms an independent monophyletic clade within Gyrodactylidea. Furthermore, the mitochondrial genome of G. pseudorasborae is the shortest in the Gyrodactylidea species compared with size differences in NCR.